Manajemen kinerja person in charge terhadap efisiensi proses celarance in dan out kapal dengan fasilitas dan infrastruktur sebagai variabel mediasi pada PT Pandawa Samudera Indonesia - Sigiro, Puja Rohani Pertiwi; Rosita, Sry; Chairunnisa, Fitri (Jurnalku, 2025)
This study aims to analyze the effect of Person in Charge performance management on the efficiency of the clearance process in and out of ships with facilities and infrastructure as mediating variables at PT Pandawa Samudera Indonesia. Data were collected through observation, interviews, questionnaires, and documentation. Data analysis used the Partial Least Square (PLS) method. The results showed that the performance management of Person In Charge has a positive and significant effect on the efficiency of the clearance process in and out of the ship, the performance management of Person In Charge has a positive and significant effect on facilities and infrastructure, facilities and infrastructure have a positive and significant effect on the efficiency of the clearance process in and out of the ship, and facilities and infrastructure mediate the effect of Person In Charge performance management on the efficiency of the clearance process in and out of the ship. Penelitian ini bertujuan untuk menganalisis pengaruh manajemen kinerja Person in Charge terhadap efisiensi proses clearance in dan out kapal dengan fasilitas dan infrastruktur sebagai variabel mediasi di PT. Pandawa Samudera Indonesia. Data dikumpulkan melalui observasi, wawancara, kuesioner, dan dokumentasi. Analisis data menggunakan metode Partial Least Square (PLS). Hasil penelitian menunjukkan bahwa manajemen kinerja Person In Charge berpengaruh positif dan signifikan terhadap efisiensi proses clearance in dan out kapal, manajemen kinerja Person In Charge berpengaruh positif dan signifikan terhadap fasilitas dan infrastruktur, fasilitas dan infrastruktur berpengaruh positif dan signifikan terhadap efisiensi proses clearance in dan out kapal, dan fasilitas dan infrastruktur memediasi pengaruh manajemen kinerja Person In Charge terhadap efisiensi proses clearance in dan out kapal.